P-676 Comparison of hCG triggering versus hCG in combination with a GnRH agonist: a prospective randomized controlled trial. (30th June 2022) - Yang, L; Luo, K; Lu, G; Lin, G; Gong, F
Abstract: Study question: Does co-administration of GnRH agonist and Human chorionic gonadotropin(dual trigger) in PGT cycles improve the number of usable blastocysts per patient compared to hCG alone? Summary answer: Using the dual trigger has no effect on the number of usable blastocysts undergoing the GnRH-ant protocol for PGT compared to triggering with hCG alone. What is known already: HCG is used at the end of controlled ovarian hyperstimulation as a surrogate LH surge to induce final oocyte maturation. Recently, based on retrospective studies, the co-administration of GnRH agonist and hCG for final oocyte maturation (dual trigger) has been suggested to improve IVF outcome and pregnancy rates. Study design, size, duration: A prospective, randomized, open-label controlled clinical trial (ChiCTR-ICR-2000031342), enrolled patients attending our university affiliated Infertility and IVF center (the Reproductive and Genetic Hospital of CITIC-Xiangya, China) between August 2020 and June 2021. This sample size achieves with a power of 80%, at a significance level(α) of 0.05. A sample size of 160 patients, 80 randomized to each group, was chosen to allow for those 10% dropped out. Participants/materials, setting, methods: The inclusion criteria for participating were: women age 20–35years, AMH≥1.2ng/ml and /or AFC ≥5, Couples with PGT-SR preimplantation genetic testing for chromosomal structural rearrangements (patients with abnormal chromosomal structure only in male or female), undergoing one of their first PGT cycle attempts. Patients fulfilled the criteria on the trigger day were randomly assigned to receive hCG or the dual trigger for final oocyte maturation. The primary outcome was the number of usable blastocysts per patient. Main results and the role of chance: 160 patients were included in the study. The age (29.1 years versus 29.4 years), BMI (22.1 kg/m2 versus 21.9 kg/m2) and the AMH (5.3 ng/ml versus 5.3 ng/ml) were comparable between the two groups. Based on PP analysis, there were no statistical difference in the number of eggs retrieved (17.1 versus 15.9), the MII oocytes (13.3 versus 12.5), the number of usable blastocysts per patient (5.0 versus 4.6) and top-quality blastocysts per patient (3.4 versus 3.2) between the two groups. Limitations, reasons for caution: None Wider implications of the findings: The enhanced response observed with the dual trigger might lead to better IVF outcomes were it used more widely. Trial registration number: ChiCTR-ICR-2000031342